Investigating tight junction proteinrelated regulation of nasal epithelial barrier integrity in allergic rhinitis patients and non-allergic individuals - Othman, Siti Sarah Che (2023)
Allergic rhinitis (AR) is an allergic disease affecting a huge population worldwide. Despite not being fatal, it has a significant impact on the quality of life. The nasal epithelial barrier is considered crucial for the first line of defence in the upper airway as it protects the host immune system from exposure to allergens. Defective tight junctions (TJs) contribute to nasal epithelial barrier dysfunction in moderate-severe AR patients. However, the association of nasal epithelial TJs, zonula occludens (ZO) proteins and histone deacetylases (HDACs) with the demographical, clinical and environmental characteristics of AR patients remains unclear. In this study, we aimed to investigate the mRNA expression of ZO-1, ZO-2, ZO-3, HDAC1 and HDAC2 in nasal epithelial cells of house dust mites (HDMs)-sensitised AR patients compared to non-allergic controls. We also examine the association between ZO-1, ZO-2, ZO-3, HDAC1 and HDAC2 levels in nasal epithelial cells with the demographical, clinical and environmental parameters of AR patients and non-allergic controls. The recruited subjects consisted of 28 AR patients and 28 non-allergic controls. A Skin prick test (SPT) was performed on the subjects to determine whether they were allergically sensitised to either one of the HDM allergens. We started this study by collecting nasal epithelial cell samples from all the subjects. The RNA samples were reverse transcribed into cDNAs for measurement of ZO-1, ZO-2, ZO-3, HDAC1 and HDAC2 expression levels by quantitative real-time polymerase chain reaction (qRT-PCR). The mRNA expression of ZO-1 was significantly decreased in AR patients compared to non-allergic controls (p=0.010). No significant difference was observed in the expression levels of ZO-2, ZO-3, HDAC1 and HDAC2 in AR patients compared to non-allergic controls. However, we found a significant association of higher HDAC2 levels in AR patients sensitised to Dermatophagoides farinae (D. farinae) (p=0.041). We also found significant associations of higher HDAC2 levels in AR patients with lower frequency of changing bedsheet (p=0.043). Higher expression of ZO-2 was observed in AR patients who had pets (p=0.007). In conclusion, our data indicated that ZO-1 expression was lower in AR patients, contributing to decreased nasal epithelial barrier integrity. In addition, we also demonstrated a correlation between the mRNA expression of ZO-2 and HDAC2 in nasal epithelial cells with specific environmental parameters. Furthermore, the presence of allergens in the bedsheet also leads to an increase in HDAC2 expression, which may affect ZOs expression in nasal epithelial barrier. Targeting the nasal epithelial barrier by restoring ZO-1 expression may be a promising therapeutic approach for AR patients.